Fretantes Romeiras: Resistência e Protagonismo Feminino nas Romarias de Juazeiro do Norte, Ceará, Brasil - Antonio Braga (Ciências Sociais Unisinos)
The article focuses on the feminine protagonism within the Juazeiro do Norte pilgrimages, Ceará, Brazil. The objective is to show how certain women - leaders of groups of pilgrims named “fretantes” - construct and play social roles within these pilgrimages that make them their protagonists. The term protagonism in the article should not be read as something that refers to the idea of visibility within the scenario in question. These women and their importance for the pilgrimages go unnoticed by the vast majority of the actors who are not specifically necessarily pilgrims. The term protagonist should be understood as something which refers to their relevance regarding the existence, continuity and internal dynamics of these pilgrimages. As well as the way they manage their feminine and leadership roles in the pilgrimages.